Master Builders' design skills in diagnosing the failures - Arun, G. (CRC PRESS-TAYLOR & FRANCIS GROUP, 2013)
Vulnerability of ancient masonry structures to dynamic actions in seismic areas, are mostly due to the ageing, environmental factors and lack of knowledge in the interpretation of the building construction methods and details during intervention. The study of building construction method and structural details has a great importance in the mechanical and dynamic behavior of a building. The main objective of this paper is to point out the importance of acknowledging the design skills of master builders during diagnosis of the failures in historic buildings. This study is made through reviewing archaeological and history of architecture publications, discussions with archaeologists and experiences met during diagnosis phase of restoration works.
Keywords: Architecture; Engineering